2023
DOI: 10.1063/5.0152782
|View full text |Cite
|
Sign up to set email alerts
|

Effect of passivation on buried interface of CsPbI2Br perovskite films

Xingming Yang,
Junjie Jiang,
Cuiping Xu
et al.

Abstract: Passivation on the surface or interface is one of the key issues in fabricating the efficient and stable perovskite solar cells (PSCs). In this Letter, we report a way to passivate the buried interface on the perovskite film by optimizing the growth kinetics of the precursor film. A solvent-controlled growth (SCG) strategy of the precursor film is adopted, that is, inducing the solvent volatilization of the precursor film before high-temperature annealing. It is found that the solvent distribution of the precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…However, the intensity has significantly increased in modified samples, indicating the inhibition of nonradiative recombination. These findings are consistent with previous research. The carrier lifetime can be derived from the decay curves of photoluminescence intensity using a biexponential decay equation: I ( t ) = I 0 + A 1 exp­(− t /τ 1 ) + A 2 exp­(− t /τ 2 ), where τ 1 and τ 2 correspond to fast decay time constants and slow decay time constants, respectively. , The average carrier lifetime (τ avg ) can be calculated as τ avg = (A 1 τ 1 2 + A 2 τ 2 2 )/(A 1 τ 1 + A 2 τ 2 ). For the TRPL measurements, the PL lifetimes of modified perovskite films are consistently longer than those of the control sample (Table ).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…However, the intensity has significantly increased in modified samples, indicating the inhibition of nonradiative recombination. These findings are consistent with previous research. The carrier lifetime can be derived from the decay curves of photoluminescence intensity using a biexponential decay equation: I ( t ) = I 0 + A 1 exp­(− t /τ 1 ) + A 2 exp­(− t /τ 2 ), where τ 1 and τ 2 correspond to fast decay time constants and slow decay time constants, respectively. , The average carrier lifetime (τ avg ) can be calculated as τ avg = (A 1 τ 1 2 + A 2 τ 2 2 )/(A 1 τ 1 + A 2 τ 2 ). For the TRPL measurements, the PL lifetimes of modified perovskite films are consistently longer than those of the control sample (Table ).…”
Section: Resultssupporting
confidence: 90%
“…In the magnified [110] pesks in Figure b, it is found that the diffraction peaks shift to small angles as the concentration of SnBr 4 increases, which indicates that part of Sn 4+ has entered the lattice gap of CsPbBr 3 , causing the crystal lattice to expand Figure c displays the transmission spectra of the samples, while absorption spectra are calculated by applying the Beer–Lambert Law: A = −log T . , The fitted band gaps are shown in Figure d, and the energy bands of all samples are approximately 2.35 eV. Spectroscopic experiments have demonstrated that the post-treatment does not affect the absorption properties of the CsPbBr 3 films.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations